DAMPAK PENERAPAN ATURAN DISPENSASI NIKAH BAGI SANTRI LKSA AL-IKHLAS PONOROGO - Bagus Putra, Imas; Salsabila, Miyah (Institut Agama Islam Riyadlotul Mujahidin, 2022)
Law Number 1 of 1974 article 7 is a special attraction for early childhood children. Even for the students of LKSA al-Ikhlas Ponorogo who are still underage on average. Mental and economic readiness is a scary thing for them. In this problem, the author uses the library method, which is to examine the law and aspects of the discussion in the PKM IAIRM HKI Study Program discussion at LKAS al-Ikhlas Ponorogo. In this discussion, it was found that in the discussion there were more shortcomings in the marriage dispensation than the advantages. In other words, there are more harms than benefits.